Risk of alanine aminotransferase flare in patients with previous hepatitis B virus exposure on biological modifier therapies—A population‐based study. (30th December 2022) - Ho, Jacky C. L.; Mak, Joyce W. Y.; Yip, Terry C. F.; Lam, Hong Man; Cheng, Tsz Yan; Lam, Tsz On; Tam, Lai Shan; Law, Man Fai; Cheung, Carmen K. M.; Ng, Siew C.; Wong, Vincent W. S.; Wong, Grace L. H.
Abstract: Background: It is uncertain whether biological therapies would increase the risk of hepatitis among patients with past hepatitis B virus (HBV) infection. This study aimed to evaluate the risk of alanine aminotransferase (ALT) flare in patients with past HBV infection while using biological therapies. Methodology: Patients who received biological therapies for ≥3 months from 2000 to 2019 were identified from a population‐based database in Hong Kong. Patients with past HBV infection were compared with a control group without prior HBV exposure. The primary endpoint was development of ALT flare within 5 years of starting biological therapies, defined as ALT >80 IU/L. Results: There were 2471 and 2394 patients with and without past HBV infection respectively. There was a non‐significant increase in risk of ALT flare among the HBV‐exposed group (27.6% vs. 23.7%, p = .055). In multivariable analysis, using prednisolone‐equivalent dose of >20 mg daily, male sex and concomitant immunosuppressants were risk factors for ALT flare. The risk of ALT flare was significantly higher with anti‐CD20 when compared to other biological agents (36.1% vs. 14.5%, p < .01), but was not significantly different among anti‐tumour necrosis factor, anti‐cytokine, Janus kinase inhibitors and T cell/B cell inhibitors or anti‐integrin (15.2% vs. 14.6% vs. 11.7% vs. 11.1%, p = .82). Among patients with documented hepatitis B surface antigen seroreversion, 96% were on anti‐CD20. Conclusions: Our study further supports the current suggestion of prophylactic anti‐viral before starting anti‐CD20 in HBV‐exposed patients. While other biological therapies appear to have a lower risk for ALT flare, this result needs further confirmation.